Bias Manajemen Penggunaan Masukan dalam Usahatani Bawang Merah (Allium ascalonicum L) - WIDYANTARA, WAYAN; YASA, NENGAH SUDIRTA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.2, No.1, Januari 2013, 2013)
Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} ABSTRACT Management Bias of Input Usage in Shallots Farming Onion, as one of the type of vegetable is much used in the Indonesian households, including in the Balinese households. In Bali the increase in population and the development of tourism contributed to the increase in the demand for onion. With its 3.5 millions heads of population, 15,960 kilogram of onion were comsumed in Bali per year. However, the production during dry season and wet season, especially in Bali, fluctuated. This study aimed at explaining the management of the allocation of production input in the farm enterprice of onion in dry season and wet season. In addition, it also aimed at explaining the bias toward the management of input on the management of farm enterprice during wet season and that during dry season, and identifying which one used production input more efficiently. The result of analysis showed that the management of onion farm enterprice in the area where the research was conducted during dry season was different from that during wet season. The width of the farm, the seed and pesticide used during dry season still contributed to the increase in production. However, during dry season the only the labor and pesticide used contributed to the increases in production. The width of the farm, the labor and pesticide used got biased, but the other factor did not. The onion farm enterprice during dry season was relatively more efficient that during rainy season; however, to what extent the efficiency was, could not be clearly identified. The efficient factor of input were age, education, experience, hired labor, the distance from Lake Batur, and the used of fertilizer. Keyword: farm enterprise, onion, management, production bias, technical efficiency.